«Being Together» in Pandemic Conditions: Social Cohesion Challenges of the Contemporary Ukrainian Society - DeinekoОleksandra (Ukrainian Sociological Journal, 2021)
The article is dedicated to the analysis of the Ukrainian society social cohesion challenges in the pandemic conditions of digitally mediated interactions. Based on the results of qualitative sociological research, as well as a secondary analysis of the results of other sociological studies and statistics data, the author explores the phenomenon of social cohesion in the unity of three social levels of its presence - macro, meso and micro. The study has shown the dialectical nature of social cohesion and the opposite tendencies of its reproduction at different social levels – inner circle, professional communities and society as a whole. In the macro-social perspective, the pandemic has become a «common challenge», intensifying social consolidation at the level of civil society institutions; on the other hand, it has created a new axis of social inequality, deepening local differences and awareness of the different degree of «protection» from crisis conditions. It is concluded that the digitally mediated everyday interactions, characterized by a lack of social actors’ co-presence in space and time, contributes to the spread of systemic integration in those social systems for which it was previously uncharacteristic. This, in turn, leads to the «frozen» functioning of social systems. In contemporary digital age, social actors are increasingly beginning to experience «digital loneliness» due to the loss of coexistence in physical time and space and the weakening of binding social capital, making familiar identification patterns less stable and definite. The «shift» of the concentration of interactions from different social circles to the level of the inner circle – the family one sets a double scenario of its reproduction either as a space of cohesive values, the highest level of trust, participation and social security, or as an environment for everyday conflicts. The article emphasizes the urgency of further conceptualization of a new type of capital – digital, which in conditions of systemic integration of social systems «puts into action» the activation of other types of capital.